Antimicrobial stewardship in transplant patients. Issue 4 (August 2019) - Hand, Jonathan; Patel, Gopi
Abstract : Purpose of review: To provide an update on the current landscape of antimicrobial stewardship in solid organ transplant (SOT) recipients. Recent findings: Constructing personalized antimicrobial prescribing approaches to avoid untoward consequences of antimicrobials while improving outcomes is an emerging and critical aspect of transplant medicine. Stewardship activities encompassing the specialized interests of transplant patients and programs are evolving. New literature evaluating strategies to optimize antimicrobial agent selection, dosing, and duration have been published. Additionally, consensus guidance for certain infectious clinical syndromes is available and should inform institutional clinical practice guidelines. Novel metrics for stewardship-related outcomes in transplantation are desperately needed. Though exciting new molecular diagnostic technologies will likely be pivotal in the care of immunocompromised patients, optimal clinical adaptation and appropriate integration remains unclear. Important studies understanding the behaviors influencing antimicrobial prescribing in organizational transplant cultures are needed to optimize interventions. Summary: Consequences of antimicrobial use, such as Clostridiodes difficile and infections with multidrug-resistant organisms disproportionately affect SOT recipients and are associated with poor allograft and patient outcomes. Application of ASP interventions tailored to SOT recipients is recommended though further studies are needed to provide guidance for best practice.